Workshop Karya Tulis Ilmiah: Penulisan Cerdas Menggunakan VOS Viewer, Connected Paper, dan Mendeley - Nugroho, Handi; Nasution, Rivara; Hamidi, Kurniawan; Saputri, Anggraini; Winanti, Famila; Kurniadi, Deri; Agusta, Huda; Azharman, Zefri; Gunawan, Aldiyanto; Chang, Winlie; Chandra, Joni; Susanti, Tri (Journal of Social and Community Service, 2024)
Scientific writing can be in the form of scientific articles, final reports, publication manuscripts, research reports such as theses, theses or dissertations. In writing scientific papers, modern reference management, such as Mendeley, Vos Viewer, and Connected Paper, has become a tool for scientific work writers to import, organize, search for references and research gaps quickly, it also makes it possible to organize and store all documents related to the project research in one place. Of the 35 participants who took part in the workshop, participants assessed that the material was delivered well by 3 resource persons, with evidence of an average rating for each resource of 4.5 on a scale of 1-5 (very bad to very good) and a standard deviation of 0.4 to 0.61. The distribution of results for the advanced themes that participants are interested in implementing in the future is optimization towards the industrial era 5.0 with an answer percentage of 54.29%; Publication of accredited scientific papers with a percentage of 25.71%; Industrial Sustainability was 11.43% and Industrial Innovation Technology was 8.57%.